2001
DOI: 10.1902/jop.2001.72.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation and Comparison of 2 Topical Anesthetics for Pain Caused by Needle Sticks and Scaling and Root Planing

Abstract: LDS is more effective than BGP for topical pain suppression to Ns and SRP in both arches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…There is a substantial number of studies on benzocaine with varying designs and conflicting results. 2,3 Some studies reported a good effect, 1,4 whereas others have shown that benzocaine is not particularly efficacious. 2,[5][6][7] Traditionally, clove has been used as a spice in cooking, but it has also been used for the topical treatment of toothache because it contains eugenol, an oily liquid that is widely used in dentistry for analgesic and antiseptic properties.…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial number of studies on benzocaine with varying designs and conflicting results. 2,3 Some studies reported a good effect, 1,4 whereas others have shown that benzocaine is not particularly efficacious. 2,[5][6][7] Traditionally, clove has been used as a spice in cooking, but it has also been used for the topical treatment of toothache because it contains eugenol, an oily liquid that is widely used in dentistry for analgesic and antiseptic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pain suppression following the use of topical anesthetics has been reported to be highly variable 16 . There are a number of different types of topical anesthetic agents for intraoral use.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is a subjective response either in degree or just in determining its presence or absence 16 . Topical anesthetics have been utilized in dentistry to reduce pain psychologically and physiologically 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that there are no significant differences when compared to the placebo. [2][3][4][5] On the other hand, there are several studies that support the efficacy of topical anesthetic. 3,[6][7][8][9] Duration of application has been isolated as an important factor to achieve adequate topical anesthesia.…”
mentioning
confidence: 99%
“…[2][3][4][5] On the other hand, there are several studies that support the efficacy of topical anesthetic. 3,[6][7][8][9] Duration of application has been isolated as an important factor to achieve adequate topical anesthesia. Meechan 10 summarizes that the degree of topical anesthesia penetration and its effectiveness are governed by the duration of application.…”
mentioning
confidence: 99%